(untitled) - Faroqhi, Suraiya (Cambridge,New York, 1999)
In a state-of-the art introduction to Ottoman history, Suraiya Faroqhi explores the documentary sources and explains how to interpret them to students in the field and in related disciplines. By considering both archival and narrative sources, she demonstrates why they were prepared, encouraging her readers to adopt a critical approach to their findings. While the book is essentially a guide to a complex discipline for initiates into the field, the experienced Ottomanist will find much that is original and provocative in its sophisticated interpretation
Keywords: Turkey,Thổ Nhĩ Kỳ; History,Lịch sử; Ottoman Empire, 1288-1918,Thời kỳ 1288-1918